Break Point: The Challenges of Teaching Multicultural Education Courses - Arlette Ingram Willis; Shuaib J. Meacham (Journal of the Assembly for Expanded Perspectives on Learning, 1996)
Teaching multicultural education courses to preservice teachers exacts an emotional toll as they begin to acknowledge their ethnic awareness.